Double Surface LED Phototherapy as an Effective Alternative to Exchange Transfusion in Neonatal Jaundice - Jahan, Ishrat; Akter, Jesmine; Shetu, Tanima Mahmud; Sultana, Zakia; Yasmeen, B H Nazma (Northern International Medical College Journal, 2025)
Background: Neonatal jaundice is a common condition may progress to severe hyperbilirubinemia requiring exchange transfusion (ET). This study evaluates the efficacy and safety of double-surface LED phototherapy as a substitute for ET in clinically significant neonatal jaundice. Methods: This retrospective observational study included 52 neonates admitted with neonatal jaundice to Bangladesh Specialized Hospital between July 2024 and January 2025. Patients were categorized based on whether they received single- or double-surface LED phototherapy. Data on bilirubin levels, treatment duration, complications, neurological outcomes, and ET requirement were collected and analyzed using SPSS version 25. Results: Double-surface phototherapy was used in 67.3% of cases and led to a significantly higher bilirubin reduction within 24 hours (mean 8.80 ± 2.60 mg/dL) compared to single-surface therapy (3.36 ± 1.27 mg/dL; p<0.0001). Hospital stay was shorter in the double-surface group (18.7 ± 6.24 vs. 56.4 ± 4.8 hours). Among 17 neonates with total serum bilirubin (TSB) ≥20 mg/dL, none required ET following double-surface phototherapy. No neurological abnormalities or severe complications were observed in either group. Conclusion: Double-surface LED phototherapy is an effective, safe, and non-invasive treatment that can serve as a viable alternative to exchange transfusion for high-risk neonatal jaundice, especially in low-resource settings. Northern International Medical College Journal Vol. 16 No. 1-2 July 2024-January 2025, Page 716-720